EXPLORING EFL STUDENTS’ PERCEPTIONS ON THE USE OF MOOC AS AN INSTRUCTIONAL MEDIA IN ONLINE CLASSES - Hairatul Hasanah; Akhmad Ali Mirza; Hesty Widiastuty (IKIP Siliwangi, 2023)
Many media have been used for online learning and are familiar because during the pandemic schools and campuses around the world carry out online learning. Therefore, the use of online media in the form of websites and Apps in online learning is very important. Instructional media used in teaching will affect students both in terms of effectiveness in online learning and in terms of student understanding of a lesson. This study aimed to determine EFL students' perceptions on the use of MOOC as an instructional media online in English for Specific Purposes (ESP) classes for students of the English Education Study Program at the IAIN Palangka Raya. This research used quantitative methods with survey research as the design. The population of this research was students of the English Study Program of 2018 who have carried out online classes for 1 semester in ESP courses at IAIN Palangka Raya. The instrument of this research was a questionnaire that was formed in the form of a Likert Scale. The researcher used a purposive sampling technique with several sample criteria. A total of 57 students answered the questionnaire in order to complete the research objectives. Data analysis was performed by calculating the data using the SPSS formula (Mean, Median, Mode, and Standard Deviation). The research findings indicated that MOOC can be good as instructional media online in English for Specific Purposes (ESP) classes, especially for EFL students with the final result of the questionnaire which consists of 16 items was 73%, and belongs to the positive or Agree category. Keywords: Perceptions; MOOC; Online Classes